Post-translational Regulation of GLT-1 in Neurological Diseases and Its Potential as an Effective Therapeutic Target - Peterson, Allison R.; Binder, Devin K. (Frontiers in Molecular Neuroscience, 2019)
Glutamate transporter-1 (GLT-1) is a Na+-dependent transporter that plays a key role in glutamate homeostasis by removing excess glutamate in the central nervous system (CNS). GLT-1 dysregulation occurs in various neurological diseases including Huntington’s disease (HD), Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and epilepsy. Downregulation or dysfunction of GLT-1 has been a common finding across these diseases but how this occurs is still under investigation. This review aims to highlight post-translational regulation of GLT-1 which leads to its downregulation including sumoylation, palmitoylation, nitrosylation, ubiquitination and subcellular localization. Various therapeutic interventions to restore GLT-1, their proposed mechanism of action and functional effects will be examined as potential treatments to attenuate the neurological symptoms associated with loss or downregulation of GLT-1.